2018
DOI: 10.1123/jcsp.2017-0054
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Evaluation of an Optimization Approach to Mental Health and Sport Performance

Abstract: Athletes experience unique stressors that have been indicated to compromise their mental wellness and sport performance, yet they underutilize mental health services. Indeed, very few mental health interventions for athletes have been developed to fit sport culture, and well-controlled mental health outcome research in athlete populations is warranted. In this randomized controlled trial, a sport specific optimization approach to concurrent mental health and sport performance (The Optimum Performance Program i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 69 publications
1
86
0
Order By: Relevance
“…The development of youth-specific models of mental healthcare for those under 25 years has resulted in decreased stigma and service barriers, improving access to evidence-based intervention 91. Athlete-specific models of care are emerging,92 and efforts to consolidate and expand such initiatives warrant the support of governing bodies, codes, and competitions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of youth-specific models of mental healthcare for those under 25 years has resulted in decreased stigma and service barriers, improving access to evidence-based intervention 91. Athlete-specific models of care are emerging,92 and efforts to consolidate and expand such initiatives warrant the support of governing bodies, codes, and competitions.…”
Section: Discussionmentioning
confidence: 99%
“…The single included intervention study was a small RCT testing a mindfulness-acceptance–based approach 94. While other groups have developed athlete-specific mental health interventions (eg, the athlete optimisation approach for college athletes of Donohue et al ),92 anxiety outcomes of these interventions are yet to be explored. The present results highlight the urgent need for well-conducted intervention-based RCTs, and specific attention towards the acceptability and efficacy of psychotherapy approaches among elite athletes is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Though beyond the scope of the present study, use of the APSQ alongside athlete-specific wellbeing interventions (e.g. Donohue et al, 2015Donohue et al, , 2018 may assist in determining the influence of scale domains on psychosocial and athletic functioning. If problems related to Self-Regulation and External Coping are associated with higher levels of psychological strain in athletes, it stands to reason that currently injured athletes would report higher scores on these factors, in addition to the athlete-specific Performance factor.…”
Section: Discussionmentioning
confidence: 99%
“…In addressing the current research gap, a promising recent RCT of The Optimum Performance Program in Sports (TOPSS) intervention (Donohue et al, ) recruited 74 collegiate athletes in the United States, 59 of them reported a previous or current mental health disorder. Rather than focusing on the reduction of psychopathology, TOPSS employed an “optimisation” approach, emphasizing the role that increased general well‐being can have on sporting performance.…”
mentioning
confidence: 99%
“…In addition, well-designed RCTs targeting common mental health disorders for athletes need to be conducted to better understand how to minimize athlete distress. It is likely that commonly used interventions seen in general clinical practice need to be adapted to be more sportspecific to achieve traction with athletes and coaches (Donohue et al, 2018;Moesch et al, 2018). Last, focusing on mental health in elite athlete populations may be an influential element of empowering those who may have previously been hesitant to seek help.…”
mentioning
confidence: 99%